2010
DOI: 10.1189/jlb.0510253
|View full text |Cite
|
Sign up to set email alerts
|

Loss of TRPC1-mediated Ca2+ influx contributes to impaired degranulation in Fyn-deficient mouse bone marrow-derived mast cells

Abstract: MC degranulation requires the influx of calcium from the extracellular environment. Orai1/STIM1 is essential to MC SOCE, as shown in rat peritoneal MCs, the rat MC lines (RBL-2H3), or in Orai1 null embryo liver-derived, cultured MCs. However, minimal information exists about the role of other calcium channels expressed on these cells. Here, we demonstrate that the nonselective TRPC1 participates in FcεRI-mediated calcium entry in mouse BMMCs. We found that Fyn null MCs, which have an impaired degranulation res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
61
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(68 citation statements)
references
References 70 publications
7
61
0
Order By: Relevance
“…We found that granule exocytosis occurs more frequently along extended cell protrusions when Ca 2+ waves initiate from these structures, particularly at limiting antigen concentration. Under these conditions, Ca 2+ influx through TRPC1 contributed significantly to granule exocytosis in these cells, consistent with our previous results indicating its participation in Ca 2+ wave initiation from protrusions (Cohen et al, 2009) and with recent evidence for its role in stimulated degranulation in mouse bonemarrow-derived mast cells (Suzuki et al, 2010).…”
Section: Discussionsupporting
confidence: 79%
“…We found that granule exocytosis occurs more frequently along extended cell protrusions when Ca 2+ waves initiate from these structures, particularly at limiting antigen concentration. Under these conditions, Ca 2+ influx through TRPC1 contributed significantly to granule exocytosis in these cells, consistent with our previous results indicating its participation in Ca 2+ wave initiation from protrusions (Cohen et al, 2009) and with recent evidence for its role in stimulated degranulation in mouse bonemarrow-derived mast cells (Suzuki et al, 2010).…”
Section: Discussionsupporting
confidence: 79%
“…2ϩ influx, F-actin depolymerization, and subsequent degranulation in activated mast cells (27). Considering that STAT5 tyrosine phosphorylation is an early response to Fc⑀RI engagement, it was important to determine whether TRPC1 has any input in this activation.…”
Section: Lack Of Transient Receptor Potential Channel 1 (Trpc1) Doesmentioning
confidence: 99%
“…PI3K is crucial for the propagation of the Fyn cascade, since it induces the activation of Akt, the production of PIP 3 (by phosphorylation of PIP 2 ), and thereby provides tethering to the Tec kinase Btk. Fyn appears to be important in the calcium influx signaling deriving from the activation of nonselective Ca 2+ channels, such as TRPC-1 [20], which contributes to store-operated calcium entry. Fyn signaling may be finely-modulated by the action of membrane phosphatases, such as the SHPs, which have been the object of investigation in a series of recent papers [21][22][23].…”
Section: Fynmentioning
confidence: 99%